2019
DOI: 10.3390/pr7100743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Assisted Ultrasonication and Ozone Pretreatments on Sludge Characteristics and Yield of Biogas Production

Abstract: The effects of ultrasonic and ozonation pretreatments on organic solubilization, anaerobic biodegradability, and biogas production were elucidated in this study. Two pretreatment methods for batch anaerobic digestion for biogas recovery with the same material and experimental conditions were the focus for comparison. Anaerobic digestion experiments were conducted at ambient temperature with the solid retention time set to 25 days. The obtained results indicated that the soluble chemical oxygen demand increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…The enhancement effect of thermal pre-treatment on the activated sludge solubilisation and thus the anaerobic digestion biodegradability was also noted by Bougrier et al [20]. In a recent study, Le et al [21] has also demonstrated that the biodegradability and thus the biogas production from anaerobic digestion increased with sludge solubilisation. Thus, the LA and LC can be mixed with FW A as feed for anaerobic digestion to produce biogas for power generation.…”
Section: Properties Of Autoclaved and Condensed Liquid Productsmentioning
confidence: 55%
“…The enhancement effect of thermal pre-treatment on the activated sludge solubilisation and thus the anaerobic digestion biodegradability was also noted by Bougrier et al [20]. In a recent study, Le et al [21] has also demonstrated that the biodegradability and thus the biogas production from anaerobic digestion increased with sludge solubilisation. Thus, the LA and LC can be mixed with FW A as feed for anaerobic digestion to produce biogas for power generation.…”
Section: Properties Of Autoclaved and Condensed Liquid Productsmentioning
confidence: 55%
“…Pot ale samples were treated with 1M NaOH first, then beaten for 0, 7.5, and 15 min. The required ratio of sample and sludge (10, 30, and 50% sludge) for 400 mL of total volume were place into 500 mL conical flasks and AD experiments were performed at three different temperatures under mesophilic conditions (32,35, and 38 • C), as specified in Table 1. All experiments were performed in triplicate as indicated for each parameter (beating time, sludge percentages, and temperature).…”
Section: Doe For Ad Of Pot Ale and Pot Ale And Spent Grain MIX (5:1 Bmentioning
confidence: 99%
“…Removing lignin increases the reactivity of the remaining polysaccharides [26] since biodegradability of many lignocellulosic compounds are associated with the fractions of hemicellulose, cellulose, and lignin [33]. Mechanical pre-treatments increase the specific surface area of the feedstock available for the microbes as well as resulting in intracellular compound release [34,35]. Furthermore, it provides a greater digestate dewaterability and no odour generation [36].…”
mentioning
confidence: 99%
“…Other pretreatments intended for improving hydrolysis include ultrasonication, available at a commercial scale, whereas other treatment options such as microwave pre-treatment, electrokinetic and high-pressure disruption are mechanical pre-treatments studied mainly under laboratory conditions or using small scale prototypes [ 19 , 20 , 21 , 22 , 23 ]. Other pre-treatment methods include the use of chemicals—acidic, alkali, ozonation—[ 24 , 25 ], and the application of advanced oxidation processes [ 26 , 27 ], and biological options (temperature-phased anaerobic digestion and microbial electrolysis cell) [ 28 , 29 , 30 ] or combinations on any of the above to increase the effectiveness of solubilization. However, the capacity of recovering the heat of the thermal hydrolysis process makes this technology superior when evaluating the efficiency in energy use.…”
Section: Introductionmentioning
confidence: 99%